Efek Pemberian Ringkasan Materi Ceramah Terhadap Pemahaman Jamaah - Siti Maesyaroh,, Syarah (Jurnal Syntax Fusion, 2025)
Religious lectures are the main method of transferring Islamic knowledge in mosques, but their effectiveness is often hampered by long duration, material complexity, and limited capacity of worshippers. This study aims to analyze the effect of providing summaries of lecture material on congregational understanding, identify differences in congregational perceptions of lectures with and without summaries, and compile recommendations to improve the quality of congregational understanding in Mosque X. The research uses a qualitative approach with a case study method, involving 15 active worshippers and 7 mosque administrators as participants. Data were collected through in-depth interviews, participatory observations, and documentation, then analyzed using thematic analysis. The results showed that the provision of lecture material summaries made a significant contribution to three dimensions of understanding: improving conceptual understanding by providing an organized cognitive framework, strengthening the retention and ability to recall information in the long term, and encouraging the application of knowledge in daily life. Pilgrims reported higher levels of focus and engagement when lectures were summarized compared to no summary.